Safety and effectiveness of adalimumab in patients with moderate-to-severe psoriasis who had inadequate therapeutic response to prior etanercept - Ting-Shun Wang; Tsen-Fang Tsai (Wolters Kluwer Medknow Publications, 2013)
Background: Few studies exist that evaluate the therapeutic response among switchers of tumor necrosis antagonists in patients with psoriasis, especially Asian patients. Objective: This study aimed to evaluate the safety and effectiveness of adalimumab in patients with moderate-to-severe psoriasis who had inadequate therapeutic response to prior etanercept. Methods: This is a single-center, open-labeled, retrospective study on the effects of adalimumab in patients with moderate-to-severe psoriasis who had inadequate therapeutic responses to prior etanercept. We included 13 patients who had received etanercept for at least 3s months but showed inadequate therapeutic response, as defined by less than 50% improvement in psoriasis area and severity index (PASI) 50, compared to baseline after 6 months or less than PASI25 improvement after 3 months in our hospital during 2006-2012. Adalimumab 40 mg was given every other week with a loading dose of 80 mg. Patients were evaluated monthly for safety and effectiveness. PASI, physician global assessment, and scores of scalp lesions were calculated at Weeks 12 and 24. Scalp lesions were assessed separately. Results: At Week 12, one patient (7%) had at least PASI90, two (15%) had at least PASI75, four (31%) had at least PASI50, and eight (61.5%) had at least PASI25 response. At Week 24, two patients (15%) had at least PASI90, three (23%) had at least PASI75, six (46%) had at least PASI50, and nine (69%) had at least PASI25 response. No severe adverse events were recorded in our series. For scalp lesion, adalimumab showed similar efficacy to etanercept nonresponders. Conclusion: Safety profiles of adalimumab were similar to those of etanercept, and PASI50 was achieved in 46% of patients, who failed prior etanercept therapy, after 24 weeks of adalimumab treatment.